2018
DOI: 10.3390/s18082670
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Personal Health-Environment Interaction with Novel Mobile Sensing Devices

Abstract: The development of connected health devices has allowed for a more accurate assessment of a person’s state under free-living conditions. In this work, we use two mobile sensing devices and investigate the correlation between individual’s resting metabolic rate (RMR) and volatile organic compounds (VOCs) exposure levels. A total of 17 healthy, young, and sedentary office workers were recruited, measured for RMR with a mobile indirect calorimetry (IC) device, and compared with their corresponding predicted RMR v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…We found two studies examining the physiological effects of VOC exposure using portable sensors, as summarized in Table 2 . While both studies measured TVOC via portable sensors, one used a commercial device that contained a photoionization detector [ 54 ], and the other used a self-made portable device comprising an electrochemical sensor [ 53 ]. As for physiological measurements, the former measured respiratory function with a portable spirometer supervised by staff, whereas the latter measured the resting metabolic rate with a portable indirect calorimeter.…”
Section: Resultsmentioning
confidence: 99%
“…We found two studies examining the physiological effects of VOC exposure using portable sensors, as summarized in Table 2 . While both studies measured TVOC via portable sensors, one used a commercial device that contained a photoionization detector [ 54 ], and the other used a self-made portable device comprising an electrochemical sensor [ 53 ]. As for physiological measurements, the former measured respiratory function with a portable spirometer supervised by staff, whereas the latter measured the resting metabolic rate with a portable indirect calorimeter.…”
Section: Resultsmentioning
confidence: 99%
“…Deng et al demonstrated improvements in stability of thermodynamic properties of known unstable sensing materials (molecularly imprinted polymer, MIP) for a quartz tuning fork (QTF) sensor. 149 This has been reported through modification of MIP by mixing polystyrene. Their study showed the adsorption response increased with rising temperature for a new sensor, while it showed the opposite for an aged one.…”
mentioning
confidence: 99%
“…By multisensor integration in data, the multisensor could supply more reliable, feasible, and accurate information otherwise hard to obtain from any single sensors, while multisensor integration in hardware could lower cost and minimize size by sharing components. It is these advantages that portable detectors prefer for the purpose of personal exposure assessment. , Because multisensor design would enhance the affordability of portable detectors both physically and financially and expand their application and popularity, the more shared components, the more compact detector size, and the lower detector cost. Generally, sensors of different type share less components in integration than sensors of the same type.…”
mentioning
confidence: 99%